Experiencing flow while teaching and learning in individual tuition settings - Cardoso, Francisco (2012)
ABSTRACT: The possibility of flow to be experienced while teaching and learning a musical instrument had already been theoretically explored by researchers. However, no studies had yet been conducted to observe it flow experiences really occurred while those activities were being held. The nature of teaching and learning activities is different from the nature of the activities studied by researchers on flow and optimal experiences, which could might raise doubts about the possibility of flow to be experienced by teachers and students. For this exploratory study it were interviewed 14 teachers and 14 students regarding the occurrence of such experiences in instrumental lessons. Results suggest that flow-like experiences actually occur while teaching and learning. Participants descriptions suggest, though, that these experiences may have special features and may not fully fit in the typical description of flow experiences.